Evaluating the Appropriateness of Existing Health-Related Quality of Life Measures in Lichen Planus - Aoife Mahon-Smith; George Skingley; Lara Ayala-Nunes; Anjali Batish; Rosie Sharp; Christel Naujoks; Eva Schruf; Nicolò Compagno; Santiago G. Moreno (Adis, Springer Healthcare, 2023)
Abstract Introduction Lichen planus (LP) is an inflammatory skin disorder that can present in various forms across the body, including lesions on the skin (cutaneous LP [CLP]), scalp (lichen planopilaris [LPP]) and mucosal regions (mucosal LP [MLP]). Several existing patient-reported outcome measures (PROMs) were identified for potential use in LP clinical development programs. This study aimed to assess the content validity and psychometric measurement properties of the Dermatology Life Quality Index (DLQI), Epworth Sleepiness Scale (ESS), Scalpdex and Oral Lichen Planus Symptom Severity Measure (OLPSSM) in an LP population. Methods Patients completed the PROs at various time points as part of an international Phase 2 clinical study in adults with MLP (n = 37), LPP (n = 37) and CLP (n = 37). Test-retest reliability, construct validity and sensitivity to change were assessed. In addition, qualitative cognitive debriefing interviews were conducted with adults with MLP (n = 20), LPP (n = 19) and CLP (n = 19) in the USA and Germany to examine the PROM content validity. Results The DLQI demonstrated adequate reliability and validity, although its ability to detect change was modest and most items were considered not relevant in qualitative interviews. The ESS had good reliability but limited evidence of validity and ability to detect change. Conceptual relevance varied according to the qualitative interview data. The Scalpdex was miscellaneous across domains, but the 'Symptoms' domain performed well overall. Overall, Scalpdex concepts were reported as relevant by most LPP patients interviewed. The OLPSSM demonstrated good psychometric properties and strong evidence of content validity. Conclusions The psychometric and qualitative findings support the use of the OLPSSM and Scalpdex within specific LP subtypes but cautioned use of the DLQI. Administration of the ESS is not recommended in LP because of its poor psychometric performance. Given these limitations, further validation of non-specific disease measures is needed and/or the development of additional LP-specific PROMs. Trial Registration NCT04300296.